GEOLOGICAL INTERPRETATION OF 2D GRAVITY MODELING IN TULUNG SELAPAN AREA AND SURROUNDINGS, SOUTH SUMATRA BASIN - Eddy Mirnanda; Vera Sarah Simatupang; Harkins Prabowo (Marine Geological Institute of Indonesia, 2022)
The South Sumatra Basin is a prolific oil and gas basin. The Tulung Selapan area, which is to the east and part of the South Sumatra Basin, is considered to have hydrocarbon potential. Several sub-basins, including the South Palembang and the North Palembang sub-basins, exist in the region. One of the geophysical methods for determining the presence of sedimentary sub-basins, structural patterns, and bedrock is the gravity method. The purpose of this study is to determine the structural pattern and interpret the subsurface geological model of the Tulung Selapan area using 2D modeling. The complete Bouguer anomaly (CBA) reveals circular and relatively northwest-southeast trending patterns, ranging from +33 mGal to +62 mGal. 2D gravity forward modeling results in eight successive rock layers. From top to bottom, the uppermost layer is swamp sediment with a mass density of 2.1 g/cm3, followed successively by the sedimentary rocks of the Kasai Formation (2.28 g/cm3), the Muara Enim Formation (2.32 g/cm3), the Air Benakat Formation (2.39 g/cm3), the Gumai Formation (2.3 g/cm3), the Baturaja Formation (2.48 g/cm3), and lastly a layer with a density of 2.7 g/cm3, which represents the bedrock. Due to the limited depth of 2800 m in 2D forward modeling, it is unable to identify the source and reservoir rocks. The seal rock (caprock) is interpreted to be shale from the Gumai Formation at an average depth of 1.53 km. Based on Second Vertical Derivative (SVD) analysis, 2D modeling identifies the presence of geological structures with normal faults.